1988
DOI: 10.2337/diacare.11.10.774
|View full text |Cite
|
Sign up to set email alerts
|

Beat-to-Beat Blood Pressure Response in Asymptomatic IDDM Subjects

Abstract: Nine insulin-dependent diabetic (IDDM) patients (aged 25-37 yr) with no symptoms of autonomic neuropathy and 15 healthy control subjects (aged 26-39 yr) were studied at rest and during tests of Valsalva maneuver, deep breathing, cold pressor, and postural change from sitting to standing. Continuous (beat-to-beat) measures were taken of heart rate, systolic blood pressure, diastolic blood pressure, and skin conductance. The diabetic patients were differentiated from the control group by the following: less vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
6
2
Order By: Relevance
“…In these relatively asymptomatic patients, the exaggerated DBP response and relationship between Valsalva HR variability and DBP change was only evident by a careful analysis of the first minute of standing, before any measurement might be taken using traditional discrete cuff inflation techniques. Our results differ somewhat from a previous study, which found a smaller fall in DBP immediately after standing for younger Type I diabetic patients compared with age‐matched controls 14 . Since the present sample is different in terms of both age and type of diabetes, it is hard to draw firm conclusions regarding mechanisms for these opposite findings.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In these relatively asymptomatic patients, the exaggerated DBP response and relationship between Valsalva HR variability and DBP change was only evident by a careful analysis of the first minute of standing, before any measurement might be taken using traditional discrete cuff inflation techniques. Our results differ somewhat from a previous study, which found a smaller fall in DBP immediately after standing for younger Type I diabetic patients compared with age‐matched controls 14 . Since the present sample is different in terms of both age and type of diabetes, it is hard to draw firm conclusions regarding mechanisms for these opposite findings.…”
Section: Discussioncontrasting
confidence: 99%
“…This system provides continuous beat‐by‐beat monitoring of systolic and diastolic blood pressure and heart rate and, therefore, allows for assessment of both the acute (within the first minute) and tonic adjustments following standing. In a recent study of Type I diabetic patients, we found an altered blood pressure response to standing compared with controls 14 . The diabetic group did not show a hypotensive response but instead a smaller fall in systolic and diastolic pressure immediately after standing, indicative of subtle sympathetic neuropathy.…”
contrasting
confidence: 42%
See 2 more Smart Citations
“…Although parasympathetic neuropathy might be a DIABETES CARE, VOLUME 16, NUMBER 5, MAY 1993 primary event (20), as also indicated by the increased heart rate in our patients with autonomic neuropathy, recent studies have shown that sympathetic neuropathy may develop not only in parallel with (21) but also before parasympathetic neuropathy (22,23). The indexes of autonomic neuropathy in this study evaluated parasympathetic as well as sympathetic neuropathy.…”
Section: Results-mentioning
confidence: 95%